2017
DOI: 10.21037/jtd.2017.03.141
|View full text |Cite
|
Sign up to set email alerts
|

Integrate imaging approach for minimally invasive and robotic procedures

Abstract: Over the past two decades, robotic and minimally invasive cardiac surgery has been continuously refined and is currently an alternative to traditional open-heart surgery for some patients. The parallel evolution of imaging modalities has made robotic surgery safer and more efficient. Here, we review the preand post-operative use of computed tomography (CT) in minimally invasive and robotic cardiac procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Although not described here, computed tomography angiography with 3-dimensional reconstruction has been quite helpful in evaluating the conduit, localizing the distal target for bypass, and confirming the location for thoracotomy. 8 The authors also demonstrated temporal improvement in outcomes with increased surgeon experience. As expected, technical errors with anastomoses were associated with an increased incidence of major adverse cardiac events (10.8% vs 1.1%).…”
mentioning
confidence: 84%
“…Although not described here, computed tomography angiography with 3-dimensional reconstruction has been quite helpful in evaluating the conduit, localizing the distal target for bypass, and confirming the location for thoracotomy. 8 The authors also demonstrated temporal improvement in outcomes with increased surgeon experience. As expected, technical errors with anastomoses were associated with an increased incidence of major adverse cardiac events (10.8% vs 1.1%).…”
mentioning
confidence: 84%
“…Although MIMVr is not solely reserved for the repair of posterior leaflet prolapse, patients with isolated P2 prolapse are particularly good candidates for MIMVr ( 13 ). Patients with or without concomitant tricuspid disease, atrial septal defect, and atrial fibrillation can be considered for a port access approach ( 13 , 14 ). However, a conventional median sternotomy is often preferred in patients who require extensive concomitant procedures such as coronary bypass graft surgery, aortic valve replacement or ascending aorta replacement ( 13 ).…”
Section: Minimally Invasive Mitral Valve Repairmentioning
confidence: 99%
“…Moreover, arteries with a luminal diameter < 7 mm are poor candidates for cannulation. Therefore, minimal luminal diameter, atherosclerotic burden and tortuosity or abnormal angulation of femoroiliac vessels can be determined on CT ( 14 ). By visualizing the central veins on CT, venous stenoses and occlusions, anomalies or clots can be identified that could impair venous drainage during cardiopulmonary bypass (CPB) ( 14 ).…”
Section: Minimally Invasive Mitral Valve Repairmentioning
confidence: 99%
See 2 more Smart Citations